Complicating the conceptual language of the Bengal diaspora. Issue 3 (19th February 2017) - Keith, Michael
ABSTRACT: In celebrating the volume by Alexander, Chatterji and Jalais "The Bengal Diaspora – Rethinking Muslim Migration", this piece suggests that the text productively disturbs the central concepts of migration, diaspora and "Muslim". This opens up further discussion about how interdisciplinary scholarship might rethink the multiple temporalities and cartographies of transnational identification.